Infrastructure investment in Indonesia: A focus on ports - Colin Duffield; Felix Kin Peng Hui; Sally Wilson (Open Book Publishers, 2019)
Infrastructure Investment in Indonesia: A Focus on Ports presents an important and original collation of current material investigating the efficient facilitation of major infrastructure projects in Indonesia and Australia, with an emphasis on infrastructure investment and a focus on port planning and development. This interdisciplinary collection - spanning the disciplines of engineering, law and planning - draws helpfully on a range of practical and theoretical perspectives. It is the collaborative effort of leading experts in the fields of infrastructure project initiation and financing, and is based on international research conducted by the University of Melbourne, Universitas Indonesia and Universitas Gadjah Mada. The volume opens with a macroscopic perspective, outlining the broader economic situations confronting Indonesia and Australia, before adopting a more microscopic perspective to closely examine the issues surrounding major infrastructure investment in both countries. Detailed case studies are provided, key challenges are identified, and evidence-based solutions are offered. These solutions respond to such topical issues as how to overcome delays in infrastructure project initiation; how to enhance project decision-making for the selection and evaluation of projects; how to improve overall efficiency in the arrangement of project finance and governance; and how to increase the return provided by investment in infrastructure. Special focus is given to proposed improvements to the portal cities of Indonesia in the areas of major infrastructure project governance, policies, engagement, operation and processes. By rigorously investigating the economic, transport, finance and policy aspects of infrastructure investment, this book will be a valuable resource for policy makers and government officials in Indonesia and Australia, infrastructure investment organisations, and companies involved in exporting services between Indonesia and Australia. This book will also be of interest to researchers and students of infrastructure planning and financing, setting a solid foundation for subsequent investigations of financing options for large-scale infrastructure developments.
Keywords: 330